THE EFFECTIVENESS OF MOOD, UNDERSTANDING, RECALLING, DETECTING, ELABORATING, AND REVIEWING (MURDER) IN TEACHING READING VIEWED FROM STUDENTSâ MOTIVATION - Amumpuni, Rengganis Siwi (English Teaching Journal, 2013)
The research was conducted at the first grade of English Teaching Department Madiun in the academic year of 2012/2013. The research method was quasi experimental research. The population in this research was the first grade students of English Teaching Department of IKIP PGRI Madiun. The writer used cluster random sampling to get the sample. The sample consists of 70Â students which are divided into two classes, IA consisting 35 students as a control class and IB consisting 35 students as an experimental class. The instruments used to collect the data were reading test to get the score of reading skill and questionnaire to get the score of studentsâÂ motivation. Before the instruments were used, the tryout was done to know the validity and reliability of instruments. The writer analyzed the data in term of their frequency distribution, normality, and homogeneity. Then, the data were analyzed by using multifactoral analysis 2X2, then followed by Tukey test. The findings in this research lead to some conclusions: (1) MURDER is more effective than DM for teaching reading; (2) The students having high motivation have better reading skill than the students having low motivation; and (3) There is an interaction between teaching methods and studentsâ motivation for teaching reading. MURDER is suitable for students having high motivation and DM is suitable for students having low motivation.Key words: Teaching Reading, MURDER, DM, Studentsâ Motivation